Figuren des Fremden in der skandinavischen Gegenwartsprosa: Herbjømsrud, Hermanson, Rynell - Thomas, Seiler (Folia Scandinavica Posnaniensia, 2007)
The following paper is concerned with the figure of the stranger in texts of three contemporary Scandinavian authors (Hans Herbjomswd, Marie Hermanson, Elisabeth Rynell). Georg Simmel’s well-known formula defines the stranger as the person who comes today and stays tomorrow. This analysis focuses on the stranger as defined by Simmel, examining his narrative as well as his function in terms of content.